Towards Development, Maintenance, and Standardized Phenotypic Characterization of Single‐Seed‐Descent Genetic Resources for Lupins. Issue 7 (9th July 2021) - Kroc, Magdalena; Tomaszewska, Magdalena; Czepiel, Katarzyna; Bitocchi, Elena; Oppermann, Markus; Neumann, Kerstin; Guasch, Luis; Bellucci, Elisa; Alseekh, Saleh; Graner, Andreas; Fernie, Alisdair R.; Papa, Roberto; et al.
Abstract: Well‐characterized genetic resources are fundamental to maintain and provide the various genotypes for pre‐breeding programs for the production of new cultivars (e.g., wild relatives, unimproved material, landraces). The aim of the current article is to provide protocols for the characterization of the genetic resources of two lupin crop species: the European Lupinus albus and the American Lupinus mutabilis . Intelligent nested collections of lupins derived from homozygous lines (single‐seed descent) are being developed, established, and exploited using cutting‐edge approaches for genotyping, phenotyping, data management, and data analysis within the INCREASE project (EU Horizon 2020). This will allow us to predict the phenotypic performance of genotyped lines, and will further boost research and development in lupins. Lupins stand out due to their high‐quality seed protein (∼40% of seed dry weight) and other primary components in the seeds, which include fatty acids, dietary fiber, and minerals. The potential of lupins as a crop is highlighted by the multiple benefits of plant‐based food in terms of food security, nutrition, human health, and sustainable production. The use of lupins in foods, along with other well‐studied and widely used food legumes, will also provide a greatly diversified plant‐based food palette to meet the Global Goals for Sustainable Development to improve people's lives by 2030. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Lupin seed phenotypic descriptors Basic Protocol 2 : Lupin seed imaging Basic Protocol 3 : Standardized phenotypic characterization of lupin genetic resources grown towards primary seed increase (development of single‐seed descent genetic resources)